EFEKTIVITAS MEDIA PEMBELAJARAN BIG BOOK TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS II MADRASAH IBTIDAIYAH MUHAMMADIYAH 5 BANYUTENGAN PANCENG GRESIK - Shella Mahdiyah; Idzi Layyinnati (Jurnal Pendidikan Islam, 2025)
Indonesia's education system faces challenges in interactive learning, particularly in religious subjects such as Aqidah Akhlak. The transition to the Merdeka Curriculum encourages the use of innovative media, such as the Big Book, to address low learning outcomes. This study aims to assess the effectiveness of the Big Book in improving learning outcomes and student motivation in second-grade students at MI Muhammadiyah 5 Banyutengah. The research employs a quantitative method with a quasi-experimental design using a pretest-posttest approach on 26 students. Data were collected through tests and questionnaires and analyzed using the Shapiro-Wilk test, correlation analysis, and t-test. The results indicate that the average post-test score was 70.07 (exceeding the minimum mastery criterion of 70), showing a 35.2% increase from the pretest score (51.92). Student motivation increased by 80.77%. The Big Book was effective in enhancing learning outcomes and student participation. The implications of this study suggest that the Big Book is recommended for Islamic religious education and teacher training. However, this study has limitations, including a small sample size (26 students) and a short intervention duration (four weeks). Future research should explore long-term effects and the integration of digital technology.